2012
DOI: 10.1007/978-3-642-35179-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Model Checking Using Generalized Testing Automata

Abstract: Abstract. Geldenhuys and Hansen showed that a kind of ω-automata known as Testing Automata (TA) can, in the case of stuttering-insensitive properties, outperform the Büchi automata traditionally used in the automata-theoretic approach to model checking~ [10]. In previous work~[23], we compared TA against Transition-based Generalized Büchi Automata (TGBA), and concluded that TA were more interesting when counterexamples were expected, otherwise TGBA were more efficient. In this work we introduce a new kind of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…We have shown that TA are better than Büchi automata (BA and TGBA) when the formula to be verified is violated (i.e., a counterexample is found), but this is not the case when the property is verified since the entire product have to be visited twice to check for each acceptance mode of a TA. Then, in order to improve the TA approach, we proposed in [2] a new ω-automata for stutter-invariant properties, called Transition-based Generalized Testing Automata (TGTA) [2], that mixes features from both TA and TGBA.…”
Section: Transition-based Generalized Testing Automata (Tgta)mentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown that TA are better than Büchi automata (BA and TGBA) when the formula to be verified is violated (i.e., a counterexample is found), but this is not the case when the property is verified since the entire product have to be visited twice to check for each acceptance mode of a TA. Then, in order to improve the TA approach, we proposed in [2] a new ω-automata for stutter-invariant properties, called Transition-based Generalized Testing Automata (TGTA) [2], that mixes features from both TA and TGBA.…”
Section: Transition-based Generalized Testing Automata (Tgta)mentioning
confidence: 99%
“…In [2], we compared the LTL model checking approach using TGTA with the "traditional" approaches using BA, TGBA and TA. The results of these experimental comparisons show that TGTA compete well: the TGTA approach was statistically more efficient than the other evaluated approaches, especially when no counterexample is found (i.e., the property is verified) because it does not require a second pass.…”
Section: Transition-based Generalized Testing Automata (Tgta)mentioning
confidence: 99%
See 3 more Smart Citations